The prevalence of mesiodens in orthodontic patients in western region of Nepal - Karmacharya, Anjana; Kafle, Dashrath (Asian Journal of Medical Sciences, 2021)
Background: Mesiodens are supernumerary teeth present in the midline of the maxilla. Aims and Objective: The present study was conducted to know the prevalence of mesiodens among children aged 5 to 14 years in Pokhara, Nepal. Materials and Methods: Data was collected from 1194 orthodontic patients coming to the department of Dentistry, in Manipal Teaching Hospital from 2009 till 2019. The files were reviewed to know the prevalence, demography and the complications associated with the presence of mesiodens. Results: Our results showed that the prevalence of mesiodens was 2.84% in our population. The prevalence was significantly more among males. Children aged 10-14 years presented more than the children aged 5-10 years. Though, there were complications associated with the presence of mesiodens, none of them were symptomatic. Conclusions: Mesiodens is the most common form of supernumerary teeth in the pediatric patients which occurs as a result of genetic and environmental factors. Their early diagnosis can reduce the treatment required and therefore prevent development of associated problems in the future.